Clinical Significance and Prognosis Value of Wnt Signaling Pathway in Cervical Cancer. Issue 10 (3rd May 2017) - Bahrami, Afsane; Hasanzadeh, Malihe; ShahidSales, Soodabeh; Yousefi, Zohre; Kadkhodayan, Sima; Farazestanian, Marjaneh; Joudi Mashhad, Mona; Gharib, Masoumeh; Mahdi Hassanian, Seyed; Avan, Amir
ABSTRACT: Cervical cancer is among the most commonly diagnosed cancer in women, supporting the need for identification of novel prognostic and predictive biomarkers to predict the risk of developing of this malignancy or predict the prognosis of patients. Against this background, the activation of the Wingless‐type (Wnt)/β‐catenin pathway has been suggested as the main dysregulated pathways, which is involved in the multistep process of cervical carcinogenesis, suggesting its value as a potential biomarker or therapeutic target. The aim of current review is to give an overview about the potential application of WNT pathway and its value which is differentially expressed in cervical cancer versus non‐tumorigenic tissue as biomarker for risk stratification and predict the prognosis of patients with cervical cancer. J. Cell. Biochem. 118: 3028–3033, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Cervical cancer is among the leading cause of cancer related death in women, supporting the need for identification of novel prognostic and predictive biomarker to predict the risk of developing of this malignancy or predict the response rate. Against this background, the activation of the Wingless‐type (Wnt)/β‐catenin pathway has been suggested as the main dysregulated pathways, which is involved in the multistep process of cervical carcinogenesis, suggesting its value as a potential therapeutic target in treatment. The aim of current review is to give an overview about the potential application of WNT pathway and its value which is differentially expressed in cervical cancer versus non‐tumorigenic tissue as biomarker for risk stratification and predict the prognosis of patients with cervical cancer.